AÇÕES AFIRMATIVAS E POVOS INDIGENAS : o princípio da diversidade em questão - Elizabeteh Maria Beserra Coelho (Universidade Federal do Maranhão, 2006)
This paper analyses the affirmatives polices for the indians peoples. lt transcends the dichotomy between meritocracy and difference. lt utilizes the theorical categories citizenship, interculturality and tradition.